Scaling-up community-based resource management in Solomon Islands - Van Der Ploeg, Jan; Sukulu, Meshach; Govan, Hugh; Eriksson, Hampus (Wiley, 2024)
This perspective reflects on conservation efforts to increase the coverage of marine protected areas in Solomon Islands. We demonstrate that the current model in which international conservation NGOs provide technical and financial support to pilot projects, from which community-based resource management will spontaneously spread, is misguided. These site-based projects typically require substantial financial resources, ignore external threats to coastal ecosystems, and tend to bypass existing governance structures, which makes replication in other areas highly problematic. We argue that to effectively support indigenous peoples and local communities in the management of marine resources and, thereby, achieve biodiversity conservation outcomes at scale, it is necessary to move away from site-based conservation projects and focus instead on strengthening the capability of government agencies.